2018
DOI: 10.3989/gya.0110181
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of commercial and single-variety avocado oils

Abstract: SUMMARY:This work aimed to determine the major and minor compounds of avocado oils. Mono-varietal oils from the Bacon, Fuerte, Hass, and Pinkerton cultivars were obtained by means of an Abencor® system, while commercial oils from Brazil, Chile, Ecuador and New Zealand were purchased locally. The content of triacylglycerols, fatty acids, aliphatic and terpenic alcohols, desmethyl-methyl-and dimethyl-sterols, squalene and tocopherols were determined. The main triacylglycerols were those with ECN48. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In addition, techniques, such as ultra-high-performance liquid chromatography (UHPLC), coupled with mass spectrometry (UHPLC-MS) or a photodiode array detector (UHPLC-PDA), as well as Inductively Coupled Plasma Mass Spectrometry (ICP-MS), have been used for the identification and/or quantification of analytes, such as polyphenols, squalene and minerals, respectively [36,37]. Other analytical techniques have been used for the qualitative determination of the components present in avocado oil, including 13 C nuclear magnetic resonance spectroscopy (NMR), which has been used for the identification of its major components, including fatty acids [38]. At the same time, 1 H Nuclear magnetic resonance spectroscopy ( 1 H-NMR) has been used for the detection of the minor components present in other vegetable oils [39].…”
Section: Use Of Analytical Techniques In the Quantification Adultmentioning
confidence: 99%
“…In addition, techniques, such as ultra-high-performance liquid chromatography (UHPLC), coupled with mass spectrometry (UHPLC-MS) or a photodiode array detector (UHPLC-PDA), as well as Inductively Coupled Plasma Mass Spectrometry (ICP-MS), have been used for the identification and/or quantification of analytes, such as polyphenols, squalene and minerals, respectively [36,37]. Other analytical techniques have been used for the qualitative determination of the components present in avocado oil, including 13 C nuclear magnetic resonance spectroscopy (NMR), which has been used for the identification of its major components, including fatty acids [38]. At the same time, 1 H Nuclear magnetic resonance spectroscopy ( 1 H-NMR) has been used for the detection of the minor components present in other vegetable oils [39].…”
Section: Use Of Analytical Techniques In the Quantification Adultmentioning
confidence: 99%
“…It was reported previously by Alkhalaf et al [8] that oleic acid was the main fatty acid present in avocado oil. A typical fatty acid profile composed of palmitic (C16:0) 10-25%, oleic (C18:1) 60-80%, linoleic (C18:2) 7-20%, and linolenic (C18:3) 0.2-1% acids of avocado oil was observed by some authors [36,37].…”
Section: Fatty Acids Profile Hydrocarbon Andphytosterols Of Acetogenin-rich Extract Of Avocado Pulpmentioning
confidence: 74%
“…Recently, others range have been reported for fatty acids from several avocado oils, which include increasing the proportion of unsaturated fatty acids, and therefore their predisposition to oxidation: Palmitic at 10.0–35.2%; palmitoleic at 2.8–16.1%; stearic at 0.2–1.5%; oleic at 36.9–74%; linoleic at 6.1–21.2%; and linolenic at 0.3–2.1%. In addition, the presence of ω7, ω9, and ω11 isomers of oleic and palmitoleic acids in avocado oil has been described [ 42 ]. During the oxidation of edible oils at high temperatures (>100 °C), it has been shown that polyunsaturated fatty acids have a higher degradation rate, followed by monounsaturated fatty acids and finally saturated fatty acids [ 43 ].…”
Section: Resultsmentioning
confidence: 99%